REPORT ON THE CORINDON CRUISES - Moosa, Mohammad Kasim (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1984)
The corindon cruises were the first realization of the Cooperation on Oceanology between the governments of France and Indonesia. The name Corindon is derived from the name of French vessel